Spase-time tendencies of air temperature change in climate warming period in the territory of Ukraine - Kobchenko, Yu. F.; Kobchenko, O. Yu. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2015)
The problems of spatial and temporal characteristics of patterns in air temperature changes during the warming climate in Ukraine have been considered. After analyzing the statistics of hydrometeorological data of meteorological stations in Ukraine for 1970-2014, it has been shown that annual temperature for the 100-year period within the territory of the study has changed by 3,1-3,5 °C, and changes in monthly temperatures have showed more tangible fluctuations in air temperature and especially it is typical for the summer months, where the temperature difference between the period of warming and cooling during the months of July and August is 5.3 and 5.1 °C, respectively. Methods of mathematical statistics and, in particular, the analysis of variance indicated a temporary change in the distribution of annual and monthly temperatures and placing them on the hierarchical levels. Analysis of changes in air temperature distribution during the warming period of climate in Ukraine has showed that the average annual temperature from 1970 to 2014 in Lugansk was 8.1 °C, in Kharkov 7,4 °C in Lviv 6,7 °C. If we compare the temperature variation of the air for 40 years with these long-term studies, we arrive at the conclusion that the climate in Ukraine is gradually warming, but in the east of the country it is more pronounced. The method of spatiotemporal analysis of patterns in air temperature change during climate warming in Ukraine unifies meteorological characteristics of these years, and can be used to solve specific problems in different sectors of the economy.